Oldenlandia diffusa(Willd.) Roxb. Essential Oil from Assam, India: GC-MS Analysis and Anticancer Activity: Oldenlandia diffusa(Willd.) Roxb. and anticancer activities - Narzary, Bardwi; Tamuli, Kashyap J; Partha P. Dutta; Bordoloi, Manobjyoti; Bora, Dipsikha (Vietnam Journal of Science and Technology, 2024)
In this study essential oil from Oldenlandia diffusa (aerial parts) was extracted using hydrodistillation method. Characterization of the essential oil was done by using GC-MS analysis and identified 71 compounds. Pentacosane (13.29%), hexacosane (11.59%), tetracosane (11.18%), heptacosane (9.76%),tricosane (6.90%), phytol (5.71%), hexatriacontane (4.87%) and isophytol (4.69%) were the major compounds constituting the oil. Further, cytotoxicity of the extracted oil was observed against PA1 (Ovarian), MIAPaCa-2 (Pancreatic), A549 (Lung), MCF7 (Breast), HeLa (Cervical), HepG2 (Liver), PC-3 (Prostatic), MDA-MB-231 (Breast) cell lines. The oil exhibited dose and time dependent inhibition effects against the cancer cell lines. Best inhibition activity was observed against PA1, HeLa and PC-3 cancer cell lines. The IC50 values ranged from 24.19±0.837 - 3.12±0.126 µg/mL in PA1 cells, 51.87±3.104 - 28.95±0.76 µg/mL in HeLa cells and 52.92±1.233 - 14.62±0.465 µg/mL in PC-3 cells at 24, 48 and 72h. From the experiments, it was clear that essential oil of Oldenlandia diffusa should be further explored as an anticancer agent for developing medicinal drug.